Surface Mount Technology - Prasad, Ray P. author. aut Link
XXIV, 610 p.
Keywords: Surface Mount Technology is not a technology of tommorrow but a technology of today. It provides a quantum jump in the packaging tech nology to produce state-of-the-art miniaturized electronic products. How ever, in order to take advantage of this technology, a complete infrastruc ture must be put in place. This requires considerable investment in human and capital resources. Intel corporation has made these investments to keep its customers for components and systems on the leading edge of technology. Based on the experience of putting this infrastructure in place for system products, this book is written for managers who need to manage the risk during its implementation, and the practicing engineers who need to improve the design and manufacturing processes for improved yield and cost reduction. To accomplish this task, I have not only culled the infor mation from published materials, but have also depended on input from both my colleagues in Intel and such outside organizations as the Institute of interconnecting and Packaging electronic Circuits (IPC) , the Electronics Industries Association (EIA), and the Surface Mount Council. But the underlying basis for this book has been my first-hand experience in im plementing this technology for Intel Systems Group and my experience at Boeing, my previous employer. In a fast-changing technology like SMT, it is very easy to have obsolete information even before the book is published. For this reason, I have concentrated on the basic principles and practice of the technology.